Analisis Unsur 10A dalam Pengembangan dan Peningkatan Kualitas Desa Wisata Buluh Duri dengan Pendekatan Importance Performance Analysis (IPA) - Graceita Juliana Tampubolon; Kurnia Darmawati Halawa; Fadlan Ramadhan Siregar; Fia Methasya Hia; Helen Eli Yana Charolin; Imelda Vega Riyanti; Khairunnisa Khairunnisa; Livia Ester L. Sibuea; Osland Herijon Lingga (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2025)
Tourism is an important sector in boosting regional and national economies. As this sector develops, attention is being directed towards the development of tourism villages as a form of sustainable management of local potential, one of which is the Buluh Duri Tourism Village in Sipispis District, Serdang Bedagai Regency, North Sumatra. This village has natural and cultural tourism potential, such as Bahbolon Rafting, Taren River, Batu Nongol River, and the beauty of a typical rural landscape. This study aims to analyze the level of importance and performance of the 10A elements in the development of Buluh Duri Tourism Village and to formulate strategies for improving the quality of tourist destinations through a quantitative approach using descriptive methods and the Importance–Performance Analysis (IPA) technique. Data were obtained from 30 respondents using a 1–5 Likert scale questionnaire. The results showed that the performance of the tourism village was relatively good, with an average importance score of 3.9 and a performance score of 3.93. The highest indicators were friendly attitude and community service, with importance and performance scores of 4.2 and 4.1, respectively, indicating that social interaction was the main strength. However, accessibility and tour packages still needed improvement. Improvements in transportation access and the development of integrated tour packages are expected to strengthen competitiveness and realize Buluh Duri Tourism Village as a sustainable community-based tourism destination.